Colonial fisheries in Tarapacá, 17th century: Internal market and Christianization - Aguilar, Julio (2013)
The article propose an historical analysis of a commercial colonial initiative in the Corregimiento of Arica-Tarapacá (South of Viceroyalty of Perú) in the early seventeenth-century. Juan Donoso a Spanish neighbor (vecino) was the head of this successful economic initiative which introduced marine and agriculture products to the colonial market of the Corregimiento of Arica and of the Audiencia of Charcas. The developed of this economic network involved the work of indigenous and slaves, as well as close exchanges between native authoriries (curacas), priests and settlers. The colonial merchant Juan Donoso not only took care for his business, but also of the Andean regional evangelization. This evoke the close relationship between spiritual and material life the early colonial society. This article study historical sources about the post-toledan era emphazising the incorporation of Tarapacá into of Peruvian economic space.